Impact of urban microfinance on the livelihood strategies of borrower slum dwellers in the Dhaka city, Bangladesh - Basharat Hossain; Syed Naimul Wadood (Journal of Urban Management, 2020)
This paper scrutinizes the impact of urban microfinance on livelihood strategies of borrower slum dwellers of Dhaka, Bangladesh (with primary and secondary data). The primary data was collected through a structured questionnaire on a total of 200 sample slum households of three slums (Korail, Jurain and WASA Colony slum) of Dhaka city (by a systematic random sampling). This paper uses econometric techniques of difference in differences (DID) and the probit model to analyze the data. The key finding is that urban microfinance has a statistically significant positive impact on some income or expenditure variables such as savings, educational expenditure, and transportation expenditure, but not with regards to all the income and expenditure variables. The probability of changing occupations of the microfinance borrowers is statistically significantly higher compared to the case of the non-microfinance borrowers. Microfinance also improved housing, utility usages, water and sanitation of the borrowers compared to the case of the non-borrowers. This paper would encourage the global microfinance institutions (MFIs) to expand their activities among the urban slum dwellers to obtain positive changes in the livelihood strategies of them.